Integration of Artificial Intelligence in the Science of Tafsīr: A Critical Analysis of Opportunities and Challenges for Contemporary Quranic Studies - Yazdan Kabir; Klapdor Hammond; Ernest Drennen; Sarah Jemali; Rekha Dastyari (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2026)
The integration of artificial intelligence into Quranic studies marks a significant transformation in contemporary interpretive practices. However, existing studies remain dominated by technical and normative approaches, lacking adequate epistemological-critical analysis. This situation raises fundamental issues regarding the relationship between algorithmic logic and the interpretive principles of tafsīr, which are contextual, reflective, and historical. This study aims to critically analyze the epistemological opportunities and challenges of AI integration into tafsīr and to formulate the boundaries and epistemic functions of AI within contemporary tafsīr methodology. The study uses a qualitative-analytical approach with a critical literature study design, drawing on classical and modern tafsīr literature, the philosophy of science, and cutting-edge digital humanities studies. The analysis is conducted through a hermeneutical-critical reading and a conceptual-comparative analysis of claims of objectivity in technology and interpretive practices. The results show that AI has the potential to strengthen tafsīr studies by processing large corpora, mapping intertextuality across tafsīrs, and systematically identifying linguistic patterns in the Quran, thereby opening up previously difficult-to-reach analytical horizons. However, this study also uncovered three major challenges: the tendency to positivize meaning due to the reduction of text to data, the neglect of the historical-social context of revelation, and the reification of algorithmic output as interpretive authority. These findings highlight the structural tension between claims of AI objectivity and the interpretive nature of tafsīr. The study concludes that integrating AI should be positioned as a supporting instrument guided by critical reasoning in tafsīr to enrich contemporary Quranic studies without eroding its epistemological complexity.